Respuesta :

Answer:

f = 2/3d -3

Step-by-step explanation:

2d-3f=9

Subtract 2d from each side

2d-2d-3f=9-2d

-3f = 9-2d

Divide by -3

-3f/-3 = 9/-3 -2d/-3

f = -3 +2/3 d

f = 2/3d -3

Answer:

[tex]f=\frac{2}{3} d-3[/tex]

Step-by-step explanation:

[tex]2d-3f=9[/tex]

Solve for [tex]f[/tex] variable.

Subtract [tex]2d[/tex] on both sides.

[tex]2d-3f-2d=9-2d[/tex]

[tex]-3f=9-2d[/tex]

Divide both sides by [tex]-3[/tex].

[tex]\frac{-3f}{-3} =\frac{9-2d}{-3}[/tex]

[tex]f=\frac{-9}{3} +\frac{2}{3} d[/tex]

[tex]f=-3+\frac{2}{3} d[/tex]